Constructing Trust in Media Through Islamic Values: Countering Hoaxes and Disinformation - Wahidah Suryani; Andries Kango; Andi Akifah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this study is to find out more about the role and credibility of the media in the midst of the rise of hoaxes, fake news, and disinformation in recent years. The research method used is qualitative, using literature methods. To conduct this research, extensive literature reviews are conducted through journals, books, and other literature. The results showed that Islamic values such as honesty and accountability can be used to counter deception and disinformation, as well as promote trustworthy communication. By upholding these values, media outlets can ensure accurate news reporting and regain public trust.